Infrastructural Needs & Economic Development in Southeastern Europe: The Case of Rail and Road Transport Infrastructure - Edward Christie; Vladimir Gligorov; Mario Holzner (The Vienna Institute for International Economic Studies (wiiw), 2004)
This paper seeks to analyse the state of rail and road transport infrastructure in the Southeast European Countries (SEECs). The paper is structured in four parts. Part one summarises theoretical findings and international empirical evidence on the theory of the `Big Push', on the issues of infrastructure quality and efficiency and on the subject of liberalisation. Part two explores the current state of rail and road transport infrastructure of the SEECs in comparison with the Central and East European Countries (CEECs) and the European Union (EU) and provides information about ongoing, committed and possible new projects in the core networks of the region. Part three gives some econometric analysis concerning road infrastructure and economic development in the SEE region. Finally, part four generalises some of the findings and discusses some of the obstacles to regional infrastructure cooperation and development. The paper concludes with some policy considerations.
Keywords: H54; R40; L92; 330; Transport Infrastructure; Economic Development; South East Europe